Takhrij and Syarah Hadith of Agrotechnology Crosses in Plants - Gita Mulyani; Wahyudin Darmalaksana; Windhy Chandria (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad. about crossing plants. The method used in this research is qualitative through the approach of takhrij and sharah hadith agrotechnology. The results and discussion of this research is that the activity of crossing plants was previously considered useless but the Prophet Muhammad SAW. suggested to continue the activity if it is useful for many people. The conclusion of this study is that the activity of plant crossing is very useful and is still developing until modern times like now.